How Can Students' Learning Styles Influence English language Learning and Teaching? - مهيري رمضان, حواجلي أحمد شوقي (Revues faculté des lettres et des langues, 2016)
يجد طلبة اللغة  الانجليزية  صعوبات في  مادة اللسانيات و مواد أخرى و ذلك يعود إلى اعتمادهم على الاستاد في الشرح و المطبوعات و غيرها. في حين انه مند تطبيق نظام ال ل.م.د في 2004 لم يعد  ينظر للطلبة  متلقين بل باحثين عن المعلومة  و عناصر فاعلة في العملية التعليمية. ولتمكين هؤلاء الطلبة من التأقلم و التحصيل أكثر في هذا الوسط الجديد’ فإن هذه الدراسة خصت مجموعة (30 طالبا) من طلبة السنة الأولى باستبيان للإجابة على السؤال "أي نوع من الطلبة أنت/م". فالفرضية الأساسية لهذه الدراسة هي أن معرفة و وعي الطالب بأسلوبه في التعلم مهم جدا وهو ما يسمح له ببناء استراتيجياته التعليمية الخاصة  داخل القسم. أدت هذه الدراسة إلى استخراج ثلاثة أنواع من الطلبة في الفوج المعني.  إن تحليل النتائج و مناقشتها مكن الباحثين من استخلاص ردود فعل الطلبة و شعورهم بعد تعرفهم على أنفسهم كمتعلمين ومدى استحسانهم لاكتشافهم لعناصر الضعف و القوة في أنفسهم و كيفية استثمارها في العمل الأكاديمي.  EFL studentsusually feel lost in Linguistics and other courses because they come to the university with their traditional learning habits, such as relying on the teacher's handouts and his explanations. However, since 2004, students have not been seen as recipients of knowledge and information. The LMD model has led to irrevocable changes, especially in the learner's role: the learner has become a real knowledge-seeker. To help these students to cope with English language classes and to achieve better, the present study employed a questionnaire to find answers to the question, "What kind/type of learners are you?" Our hypothesis starts from the assumption that an awareness of the learners' learning styles is very beneficial. This study singled out three categories of learning styles from a group of thirty (30) first year students. The analysis of the results enabled the researchers to elicit the respondents' reactions and feelings about the discovery of their categories as EFL learners. The results show that students really need to discover their learning styles so as to build their learning strategies.